2019
DOI: 10.7567/1347-4065/ab07a0
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial AlN on c-plane sapphire by plasma nitriding

Abstract: Nitridation of sapphire to form epitaxial AlN by microwave plasma containing nitrogen gas has been investigated to be an efficient process. Structural characterization with chemical analysis by X-ray diffraction and X-ray photoelectron spectroscopy shows that an epitaxial AlN film containing oxygen can form on sapphire by using pure nitrogen plasma. Furthermore, nitridation with N2/H2 plasma not only improves the crystallinity of the epitaxial AlN film without oxygen, but also significantly increases the nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For subsequent annealing of the as-deposited TiHfN film, the TiHfN/Si sample was placed on a Mo holder and loaded into a microwave plasma system (ASTeX, 2.45 GHz, MA, USA). The annealing process was similar to that used for TiZrN films [24], and for plasma nitridation of sapphire and TiO 2 to obtain epitaxial AlN and TiN, as shown in our previous studies [25][26][27]. The surface of the TiHfN film was first cleaned with pure hydrogen plasma at a microwave power of 300 W and a pressure of 13 mbar for 5 min, followed by plasma annealing with a gas flow rate of 400 sccm (2.5% H 2 /N 2 ), a power of 800 W and a pressure of 90 mbar for 2 h. The temperature of plasma annealing was 1000-1100 • C, as measured by the optical pyrometer.…”
Section: Methodsmentioning
confidence: 99%
“…For subsequent annealing of the as-deposited TiHfN film, the TiHfN/Si sample was placed on a Mo holder and loaded into a microwave plasma system (ASTeX, 2.45 GHz, MA, USA). The annealing process was similar to that used for TiZrN films [24], and for plasma nitridation of sapphire and TiO 2 to obtain epitaxial AlN and TiN, as shown in our previous studies [25][26][27]. The surface of the TiHfN film was first cleaned with pure hydrogen plasma at a microwave power of 300 W and a pressure of 13 mbar for 5 min, followed by plasma annealing with a gas flow rate of 400 sccm (2.5% H 2 /N 2 ), a power of 800 W and a pressure of 90 mbar for 2 h. The temperature of plasma annealing was 1000-1100 • C, as measured by the optical pyrometer.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous reports, the AlN has two crystalline structures: a cubic structure and a hexagonal structure, and the probability of the cubic structure (c-AlN) formation is higher in plasma nitriding. 12,25) The peaks of Al…”
Section: Effect Of the H 2 Concentration On Aluminum Nitridingmentioning
confidence: 99%
“…In our recent studies, we have shown that microwave plasma can be effectively applied for nitridation of c-plane and m-sapphires to form epitaxial AlN. In addition, epitaxial TiN can obtain plasma nitridation of rutile TiO 2 [12][13][14].…”
Section: Introductionmentioning
confidence: 99%